ASSOCIATION BETWEEN THE -444C POLYMORPHISM IN THE LTC4S GENE AND COMORBIDITY RISK IN PATIENTS WITH BRONCHIAL ASTHMA - Kochuieva, Maryna M.; Psarova, Valentyna H.; Cherednychenko, Nataliia А.; Gogunska, Inna V.; Sviatenko, Tetiana V.; Klymchuk, Larisa F.; Kyrychenko, Anastasiia Y. (Eastern Ukrainian Medical Journal, 2025)
Objective: to establish associations between the polymorphic marker -444C in the LTC4S gene and the risk of developing comorbid pathology in patients with moderate bronchial asthma. Materials and Methods. For this study, we used clinical and anamnestic, anthropometric, biochemical, instrumental, medical and genetic, and statistical methods, as well as enzyme-linked immunosorbent assay. The level of asthma control was assessed using the Asthma Control Questionnaire-5 (ACQ-5). The data were analyzed using the SPSS 21.0 (IBM) statistical software and Microsoft Office Excel 2003. All participants were informed about the purpose of the study and signed written consent. Results. We examined 181 patients over 18 years with moderate persistent bronchial asthma (according to current recommendations GINA, updated 2020) with poor or no control of asthma symptoms with respiratory function limitation at < 80 % of the PEF or FEV1 reference level. The С/С genotype of the polymorphic marker -444C in the LTC4S gene was found to be associated with comorbidity risk in the subjects studied. The proportion of individuals who simultaneously have both chronic rhinosinusitis with nasal polyps and nonsteroidal anti-inflammatory drug-exacerbated respiratory disease is significantly higher among the patients with the C/C genotype (51.6%) compared to the A/A and A/C genotypes (p < 0.01). Analysis of the association between asthma and type 2 diabetes showed that patients who were carriers of the C/C genotype had a 3.75-fold increased risk of developing type 2 diabetes (OR = 3.75; 95% CI = 1.65 ÷ 8.53; p = 0.05) compared to carriers of the A/A and A/C genotypes (18% in individuals with the A/A and A/C genotypes vs. 45% in individuals with the C/C genotype). In the carriers of the C/C genotype, the risk of gastroesophageal reflux disease was 2.49 times higher (OR = 2.49; 95% CI = 1.13 ÷ 5.46; p = 0.05) compared to carriers of the A/A and A/C genotypes (30% of individuals with the A/A and А/С genotypes vs. 38.7% of individuals with the C/C genotype). The carriers of the C/C genotype had a 2.19-fold increased risk of arterial hypertension (OR = 2.19; 95% CI = 0.99÷4.84; p = 0.05) compared to carriers of the A/A and A/C genotypes (27% of individuals with the A/A and A/C genotypes vs. 45% of individuals with the C/C genotype). In the group of patients with asthma who were C/C genotype carriers, the risk of obesity increased by 2.22 times (OR (odds ratio) = 2.22; 95% CI (confidence interval) = 1.02 ÷ 4.86; p = 0.05) compared to carriers of the A/A and A/C genotypes. The prevalence of obesity in individuals with the C/C genotype was 54.4%, and in individuals with the A/A and A/C genotypes, it was 35.3%. Conclusions.The С/С genotype of the polymorphic marker -444C in the LTC4S gene is associated with a significantly higher risk of developing comorbidities: chronic rhinosinusitis with nasal polyps (3.9-fold higher risk), nonsteroidal anti-inflammatory drug-exacerbated respiratory disease (2.8-fold higher risk), type 2 diabetes (3.8-fold higher risk), obesity (2.2-fold higher risk), gastroesophageal reflux disease (2.5-fold higher risk), and arterial hypertension (2.2-fold higher risk). Assessment of comorbidities, including genetic screening, is important for the treatment of asthma patients and for predicting the course of the disease.